Beyond Competitive Dynamic Framework: Competing in Disruptive Environment - Dian Alanudin; Sari Wahyuni; Lily Sudhartio (Program Studi Manajemen Institut Manajemen Koperasi Indonesia Bandung, 2024)
The creative industry has become a hot topic in a new economy. The industry should create a competitive advantage source to “win the battle without losing its ground”. These capabilities are crucial in fostering the industry's competitive advantage in the global context. To win the battle through innovation as a first-mover, information, technology, and creative talent as valuable resources. These main drivers are important to compete in the 21st century, valuable resources, and intangible assets in fostering competitive advantage in the industry. Without this capability and skills, the firms in this industry are not easy to compete with and are difficult to develop continuously sustain growth in the industry. The purpose of this paper is to contribute by giving a critical analysis of existing phenomena and emphasizes the analyzes of Penrose, Schumpeter’s Theory, and the Action-Reaction Model in explaining the strategy dynamics integrating with the Market-Based, Industrial Organization, and the Resource-Based Theory in fostering competitive advantage. This study is based on secondary data to fill the gap in the phenomena and literature. The analyzes will shed holistic understanding and contribute some insight into creative industry perspectives and give enlightenment to other scholars, managerial implication, and all creative industry stakeholders.